The Bromodomain Containing 8 (BRD8) transcriptional network in human lung epithelial cells - Browne, James A.; NandyMazumdar, Monali; Paranjapye, Alekh; Leir, Shih-Hsing; Harris, Ann (Molecular and cellular endocrinology, 2021)
Mechanisms regulating gene expression in the airway epithelium underlie its response to the environment. A network of transcription factors (TFs) and architectural proteins, modulate chromatin accessibility and recruit activating or repressive signals. Bromodomain-containing proteins function as TFs or by engaging methyltransferase or acetyltransferase activity to induce chromatin modifications. Here we investigate the role of Bromodomain Containing 8 (BRD8) in coordinating lung epithelial function. Sites of BRD8 occupancy genome-wide were mapped in human lung epithelial cell lines (Calu-3 and 16HBE14o-). CCCTC-Binding Factor (CTCF) was identified as a predicted co-factor of BRD8, based upon motif over-representation under BRD8 ChIP-seq peaks. Following siRNA-mediated depletion of BRD8, differentially expressed genes with nearby peaks of BRD8 occupancy were subject to gene ontology process enrichment analysis. BRD8 targets are enriched for genes involved in the innate immune response and the cell cycle. Depletion of BRD8 increased the secretion of the antimicrobial peptide beta-defensin 1 and multiple chemokines, and reduced cell proliferation.